Писатели, художники, композиторы Удмуртии: [справочник / составил Емельянов М. П.] - Емельянов М. П. (Удмуртия, 1981)
Экземпляры: ИСК (20000920) / Инвентарный номер: у29697 / Сис.шифр: 8С(Удм) / Авт.знак: П 34 / ГРНТИ: 17 / ББК: 83